Customer engagement, consumption and firm performance in a multi-actor service eco-system: The moderating role of resource integration - Ho, M.H.W.; Chung, H.F.L.; Kingshott, Russel; Chiu, C.C. (2020)
© 2020 Elsevier Inc.